2018
DOI: 10.2478/orga-2018-0020
|View full text |Cite
|
Sign up to set email alerts
|

Revising the Importance of Factors Pertaining to Student Satisfaction in Higher Education

Abstract: Background and purpose: Competition among higher education institutions is intensifying and such institutions are increasingly directing efforts towards improving their ranking. In this context, both high-quality programmes and student satisfaction have become major goals of universities. In our study, we tried to identify the importance of various factors influencing student satisfaction in higher education institutions.Design/Methodology/Approach: A paper-and-pencil survey was carried out in the 2017/18 acad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…This way, the student is considered as a client who receives the services of the university as an organizational entity [1,26]. The level of satisfaction with educational experience is a very important component of the evaluation of an institution and a global sustainability factor [27]. Satisfaction is an outcome of service quality and student satisfaction has thus become one of the major goals of universities.…”
Section: Higher Education As a Service Qualitymentioning
confidence: 99%
“…This way, the student is considered as a client who receives the services of the university as an organizational entity [1,26]. The level of satisfaction with educational experience is a very important component of the evaluation of an institution and a global sustainability factor [27]. Satisfaction is an outcome of service quality and student satisfaction has thus become one of the major goals of universities.…”
Section: Higher Education As a Service Qualitymentioning
confidence: 99%
“…Scientific literature lists a variety of factors that predict student satisfaction, including the quality of the teaching–learning process [ 6 , 73 , 74 , 75 ], as well as aspects related to the educational infrastructure, such as administrative staff [ 73 , 76 , 77 , 78 ], university facilities [ 65 , 79 , 80 , 81 ], location [ 65 , 78 ] and technological resources [ 66 ]. In this sense, educational technology should be highlighted as an important factor that influences student satisfaction, both with the educational infrastructure through the availability of technological resources and the support of information technologies [ 66 ], and with the teaching–learning process, by means of the use of technological resources by teachers [ 74 ].…”
Section: Introductionmentioning
confidence: 99%
“…In relation to satisfaction with the educational infrastructure, there are multiple studies that have empirically verified that facilities are indicated as a determining element for satisfaction by students from different areas of knowledge and in different countries, taking into account various aspects: library, communal areas, computers, classroom spaces, number of students per class, accommodation services, restaurant and sports, among others [ 78 , 79 , 88 ]. Regarding satisfaction with the educational infrastructure, according to gender, some studies do not find statistically significant differences [ 79 , 89 ], while others report that women are more satisfied than men [ 73 ]. Regarding the type of institution, the majority of research shows greater satisfaction with the infrastructure in private institutions [ 75 , 76 , 90 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though many surveys mapping students' expectations towards higher education institutions and identifying the dimensions / criteria of quality of services provided by the HE have been conducted (see e.g. Wiers-Jenssen et al, 2002;Gruber et al, 2010;Tsinidou et al, 2010;Zineldin et al, 2011;Ďaďo et al, 2013;Vouneagu et al, 2017;Bell and Brooks, 2018;Jereb et al, 2018; and others) the synthesis of the obtained results is problematic. The authors who attempted to compare the studies aimed at identifying key dimensions of student satisfaction and summarizing their findings conclude that since service quality is a contextual issue, its dimensions and the definitions of the variables identified as significant predictors of satisfaction vary widely among the various studies (Gibson, 2010;Sultan and Wong, 2010).…”
Section: Introductionmentioning
confidence: 99%